Quantum potential theory - Biane, Philippe (Springer, 2017)
Potential Theory in Classical Probability -- Introduction to Random Walks on Noncommutative Spaces -- Interactions between Quantum Probability and Operator Space Theory -- Dirichlet Forms on Noncommutative Spaces -- Applications of Quantum Stochastic Processes in Quantum Optics -- Quantum Walks...